DEPRESSION & ANXIETY THE CAUSES & TREATMENT ACCORDING TO THE QURAN - Al-Buti, Muhammad Sa'id Ramadan (Nawa Books, 2023)
In a world plagued by depression and anxiety, Depression and Anxiety: The Causes and Treatment According to the Quran explores these ailments from a unique perspective. Based on the teachings of Imam Imam Muhammad Saʿid Ramadan Al-Buti, this groundbreaking book unveils hidden causes often overlooked within a secular paradigm. Delving into different types of depression and anxiety linked to specific causes, it emphasizes the role of a strengthened relationship with Allah in finding healing and empowerment. This book offers spiritual enrichment, guiding readers to lessen their attachment to this world, purify their hearts and souls, and understand the purpose of their existence. By drawing nearer to Allah and embracing the teachings of the Qurʾān, readers gain the competence and strength to face life's challenges without succumbing to anxiety or depression. With insightful appendices and additional resources, Depression and Anxiety: The Causes and Treatment According to the Qurʾān provides the tools for a deeper understanding, guiding individuals towards the emotional well-being and inner peace that comes from being close to one's Lord. And with Allah alone is every success.